An Annotated Checklist of Macrobenthic Algae of the Western Coast of Zamboanga City (Mindanao, Philippines) - Tito, O.; Sescon, C.; Adalla, C.; Asdani, J.; Basilio, E. M.; Climaco, A.; Dagalea, A.; Luna, M.; Uddin, Y.; Vega, R. A. (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Seaweed collections were made at several sites along the western coast of Zamboanga City from July to August 1999. Ninety-four (94) taxa were identified. These represent the three (3) major algal divisions broken down into fifteen (15) orders, twenty-six (26) families and forty-four (44) genera. Six species: Botryocladia leptopoda (J. Agardh) Kylin, Halimeda distorta (Yamada) Colinvaux, Halimeda melanesica Valet, Kallymenia perforata J. Agardh, Sarconema filiforme (Sonder) Kylin and Solieria robusta (Greville) Kylin, and the genus Sarconema Zanardini represent new records for Zamboanga and the Philippines. All specimens are deposited in the Zamboanga State College of Marine Sciences and Technology Herbarium.
Keywords: checklist; seaweed species; new records; Zamboanga